Web of deceit: Relationships between the dark triad, perceived ability to deceive and cyberloafing - Emily Lowe-Calverley; Rachel Grieve (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2017)
The rapid growth of digitally mediated work means that non-traditional forms of counterproductive workplace behaviours are emerging, such as cyberloafing: use of the Internet for non-work related purposes. Time lost due to cyberloafing can have substantial impact on productivity. This research was the first to investigate the mechanisms by which dark personality traits and perceived ability to deceive are associated with cyberloafing. A sample of currently or previously employed participants (N = 273), completed measures of psychopathy, Machiavellianism, narcissism, perceived ability to deceive, and cyberloafing. Path analysis was used to evaluate the model, and revealed good fit. As predicted, PATD mediated the relationships between the Dark Triad and cyberloafing, while psychopathy also related to cyberloafing directly. These findings suggest that in order to reduce cyberloafing, workplace policy should target an individual’s confidence in their ability to evade detection when misusing the Internet. Future research could strengthen the approach taken here by including a behavioural measure of cyberloafing. It is concluded that perceived ability to deceive plays a vital role in determining the way in which individuals possessing dark personality characteristics engage in technology-based counterproductive work behaviours.